2020
DOI: 10.3389/fphar.2020.00285
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside-Rb1 for Ischemic Stroke: A Systematic Review and Meta-analysis of Preclinical Evidence and Possible Mechanisms

Abstract: Background: Ischemic stroke is the most common type of stroke, while pharmacological therapy options are limited. Ginsenosides are the major bioactive compounds in Ginseng and have been found to have various pharmacological effects in the nervous system. In the present study, we sought to evaluate the effects of Ginsenoside-Rb1 (G-Rb1), an important ingredient of ginsenosides, and the probable neuroprotective mechanisms in experimental ischemic strokes. Methods: Studies of G-Rb1 on ischemic stroke animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 101 publications
1
9
0
Order By: Relevance
“…Rb1 administered on 7 consecutive days in advance significantly alleviated the LPS induced neuronal loss and improved the motor functions in LPS mice. These results not only confirm our presumption as mentioned above, but they also shed light on the findings that Rb1 improves learning and memory, as well as the sensorimotor system, in several other studies [27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…Rb1 administered on 7 consecutive days in advance significantly alleviated the LPS induced neuronal loss and improved the motor functions in LPS mice. These results not only confirm our presumption as mentioned above, but they also shed light on the findings that Rb1 improves learning and memory, as well as the sensorimotor system, in several other studies [27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…Most importantly, Rb1 is the key component for neuroprotection with a recent finding suggesting a greater neuroprotective activity for Rb1 when administered intranasally [ 37 ]. A recent review on analysis of preclinical evidence of Rb1 highlighted that its neuroprotective effect was mainly through attenuating brain water content, promoting the bioactivity of neurogenesis, antioxidative, anti-inflammatory and anti-apoptosis effects with enhanced cerebral circulation and energy supplementation [ 38 ]. In a study dealing with anti-amnestic and anti-aging effects, Cheng et al [ 39 ] demonstrated the potential of Rb1 and Rg1 to attenuate the neurogenerative disorders by increasing neural plasticity and proliferation/differentiation of neural progenitor cells in dentate gyrus of hippocampus of normal adult mice and global ischemia model in gerbils.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the main mechanisms described above, ginsenosides can also ameliorate cerebral ischemic injury by enhancing neurogenesis and regulating Ca 2+ influx into neurons (Shi et al, 2020; Xie et al, 2018). Ginsenoside Rb1 could improve functional recovery after stroke by stimulating axonal regeneration and brain repair.…”
Section: Pharmacological Actionsmentioning
confidence: 99%